2018
DOI: 10.1097/meg.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic increase in cardiovascular risk in diabetes mellitus with nonalcoholic fatty liver disease: a meta-analysis

Abstract: This is the first meta-analysis investigating the relationship between NAFLD and CVD independent of the impact of DM. Our findings suggested that NAFLD increases the risk of CVD in populations with comparable DM profiles. Diabetic patients diagnosed with NAFLD might benefit from a more early cardiovascular risk assessment, thereby reducing CVD morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 34 publications
2
66
1
3
Order By: Relevance
“…Indeed, several mechanisms correlated with NAFLD pathogenesis are involved in atherosclerosis and include genetic predisposition, reduced levels of adiponectin, IR, atherogenic dyslipidemia, oxidative stress, chronic inflammation, and altered production of pro- and anti-coagulant factors (Francque et al, 2016). Recently, a systematic review (Zhou et al, 2018) has described a two-fold increase in risk of CVD in diabetic NAFLD patients compared with non-NAFLD group, confirming other previous findings (Targher et al, 2007; Hamaguchi et al, 2007). Likewise, other two independent studies found that TG to high-density lipoprotein cholesterol ratio (TG/HDL-C) could be considered a better NAFLD predictor compared to other several lipid parameters and markers of liver injury (Ren et al, 2019; Fan et al, 2019).…”
Section: Nafld As a Risk Factor For Cardiovascular Diseasessupporting
confidence: 74%
“…Indeed, several mechanisms correlated with NAFLD pathogenesis are involved in atherosclerosis and include genetic predisposition, reduced levels of adiponectin, IR, atherogenic dyslipidemia, oxidative stress, chronic inflammation, and altered production of pro- and anti-coagulant factors (Francque et al, 2016). Recently, a systematic review (Zhou et al, 2018) has described a two-fold increase in risk of CVD in diabetic NAFLD patients compared with non-NAFLD group, confirming other previous findings (Targher et al, 2007; Hamaguchi et al, 2007). Likewise, other two independent studies found that TG to high-density lipoprotein cholesterol ratio (TG/HDL-C) could be considered a better NAFLD predictor compared to other several lipid parameters and markers of liver injury (Ren et al, 2019; Fan et al, 2019).…”
Section: Nafld As a Risk Factor For Cardiovascular Diseasessupporting
confidence: 74%
“…Elevations in alanine aminotransferase [70] and gamma glutamyltransferase [71] have been found to predict MetS. Hepatic steatosis is also known to be associated with increased cardiovascular risk including CAD [72], increased coronary artery calcium score [73], atrial fibrillation [74], and overall cardiovascular risk in diabetics [75,76].…”
Section: Eat and Liver Steatosismentioning
confidence: 99%
“…The prevalence of NAFLD among patients with diabetes mellitus (DM) may be as high as 50% . A recent meta‐analysis demonstrated a synergistic increase in cardiovascular mortality among diabetics with NAFLD . In addition, smoking has been shown to be associated with advanced liver fibrosis among NAFLD patients .…”
Section: Introductionmentioning
confidence: 99%